Spatial and attentional functions of the midbrain visual system - Foreman, Nigel (1980)
The superior colliculus of the midbrain has been implicated in spatial and attentional behaviours, in particular the redirecting of attention to novel peripheral stimuli. Paradoxically, while certain aspects of sensory and motor organisation within the structure are common to all species studied, others (eg. single unit characteristics) show wide interspecies variation. Models of intracollicular processing and possible functional subdivisions were discussed.